The Moderating Role of Environmental Performance in the Effect of Profitability, Liquidity and Growth Opportunities for Disclosure on Carbon Emissions - Aviani Widyastuti; Seva Eka Cahyani; Ihyaul Ulum (Universitas Pendidikan Ganesha, 2023)
This study aims to examine the effect of profitability, liquidity, and growth opportunity on carbon emission disclosures with environmental performance as a moderating variable. The population of this study is high-profile industrial companies listed on the Indonesia Stock Exchange (IDX), with the sample in this study being 123 high-profile industrial companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. Determination of the number of samples used purposive sampling method. The hypothesis was tested using the SPSS 26 program with Multiple Regression Analysis (Multiple Linear Regression) and Moderated Regression Analysis (MRA). The results of this study indicate that profitability and liquidity have a significant effect on carbon emission disclosures. Growth Opportunity do not have a significant effect on carbon emission disclosures. Environmental performance has a significant effect on carbon emission disclosures.